Perancangan kartu bermain bahasa Indonesia seri imbuhan me- untuk siswa BIPA - Randi Ramliyana; Retna Ningsih (Universitas Indraprasta PGRI, 2018)
Indonesian Language classes for Foreigners (SPEAKER) continues to increase every year. However, the students at the level of prapemula still have difficulty when learning the grammar subjects, especially the section prefix. SPEAKER classes is slightly different with the Indonesia language classes for native speakers. Those who learned SPEAKER is a foreigner who has never heard of and use the language of Indonesia at all. Therefore, they are very difficulty studying grammatical affixes, notably Indonesia. In this study, we designed a media learning designed to study the affixes, notably the prefix me-. Learning media that we made in the form of playing cards. As an Alliance of teachers of visual, visual media can increase 400% of the learning process of the students in the classroom. Based on the foregoing, we make playing cards-shaped Playing Cards. The purpose of this research is to design the learning media can facilitate the students learning the affixes me-SPEAKER-shaped playing cards.